Development of E‐chromosome Specific Molecular Markers for Thinopyrum elongatum in a Wheat Background. Issue 6 (1st November 2015) - Chen, Shiqiang; Gao, Yong; Zhu, Xue; Zhang, Chao; Cao, Wenguang; Fedak, George; He, Zhentian; Chen, Xiulan; Chen, Jianmin
ABSTRACT: Eleven primers were synthesized according to the reverse transcriptase and long terminal repeat (LTR) conserved regions of retrotransposons BARE ‐1 from barley (Hordeum vulgare L.) and RIRE ‐1 from rice ( Oryza sativa L.). Fifty‐two pairs of primer combinations based on these 11 primers were used for DNA amplification of Chinese Spring‐ Thinopyrum elongatum addition lines, substitution lines plus the two parents. It showed that 145 specific fragments of inter‐simple sequence repeat (ISSR), inter‐retrotransposon amplified polymorphism (IRAP), and retrotransposon microsatellite amplified polymorphism (REMAP) were obtained which distributed over all the seven E‐genome chromosomes of Th. elongatum . Sixty specific fragments of ISSR, IRAP, and REMAP were randomly selected for cloning and sequencing. Thirty‐four sequences were found not to be homologous with wheat ( Triticum aestivum L.) sequences in GenBank, which were considered to be the specific sequences of Th. elongatum . Thirty‐four pairs of primers based on these 34 specific sequences were synthesized, and 13 chromosome‐specific markers of Th. elongatum were identified and converted into SCAR markers. The results indicated that ISSR, IRAP, and REMAP techniques can be used to develop chromosome‐specific sequence‐characterized amplified regions (SCAR) markers with good stability and repeatability. These specific SCAR markers can now be used to detect Th. elongatum chromosomes and possibly even some introgressed segments in a wheat background.